Evaluation of a Pilot Asthma Care Program for Electronic Communication between School Health and a Healthcare System’s Electronic Medical Record - Reeves, Kelly W.; Taylor, Yhenneko; Tapp, Hazel; Ludden, Thomas; Shade, Lindsay E.; Burton, Beth; Courtlandt, Cheryl; Dulin, Michael (Applied Clinical Informatics, 2016)
Objective Asthma is a common childhood chronic lung disease affecting greater than 10% of children in the United States. School nurses are in a unique position to close gaps in care. Indeed, effective asthma management is more likely to result when providers, family, and schools work together to optimize the patient’s treatment plan. Currently, effective communication between schools and healthcare systems through electronic medical record (EMR) systems remains a challenge. The goal of this feasibility pilot was to link the school-based care team with primary care providers in the healthcare system network via electronic communication through the EMR, on behalf of pediatric asthma patients who had been hospitalized for an asthma exacerbation. The implementation process and the potential impact of the communication with providers on the reoccurrence of asthma exacerbations with the linked patients were evaluated.Methods By engaging stakeholders from the school system and the healthcare system, we were able to collaboratively design a communication process and implement a pilot which demonstrated the feasibility of electronic communication between school nurses and primary care providers. Outcomes data was collected from the electronic medical record to examine the frequency of asthma exacerbations among patients with a message from their school nurse. The percent of exacerbations in the 12 months before and after electronic communication was compared using McNemar’s test.ResultsThe pilot system successfully established communication between the school nurse and primary care provider for 33 students who had been hospitalized for asthma and a decrease in hospital admissions was observed with students whose school nurse communicated through the EMR with the primary care provider.Conclusions Findings suggest a collaborative model of care that is enhanced through electronic communication via the EMR could positively impact the health of children with asthma or other chronic illnesses.Citation: Reeves KW, Taylor Y, Tapp H, Ludden T, Shade LE, Burton B, Courtlandt C, Dulin M. Evaluation of a pilotasthma care program for electronic communication between school health and a healthcare system’s electronic medicalrecord.
Keywords: Childhood asthma; electronic health records and systems; messaging; provider-provider communication; school health